1986
DOI: 10.1152/jappl.1986.61.4.1475
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of wet-suit diving in Japanese male breath-hold divers

Abstract: The present study was undertaken to investigate energy balance in professional male breath-hold divers in Tsushima Island, Japan. In 4 divers, rectal (Tre) and mean skin (Tsk) temperatures and rate of O2 consumption (VO2) were measured during diving work in summer (27 degrees C water) and winter (14 degrees C water). Thermal insulation and energy costs of diving work were estimated. In summer, comparisons were made of subjects clad either in wet suits (protected) or in swimming trunks (unprotected), and in win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
13
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
9
13
1
Order By: Relevance
“…1). Kang et al (1983) and Shiraki et al (1986) reported a slower and smaller decrement of T ළ sk in wetsuit-protected divers compared with the naked condition similar to the findings of the present study. Since the TSS used in the present study was made of neoprene, similar to the wetsuits, the TSS could limit the water inflow to the clothed body parts and attenuate the convective and conductive heat loss and thus maintain a higher T ළ sk .…”
Section: Body Temperaturesupporting
confidence: 89%
See 4 more Smart Citations
“…1). Kang et al (1983) and Shiraki et al (1986) reported a slower and smaller decrement of T ළ sk in wetsuit-protected divers compared with the naked condition similar to the findings of the present study. Since the TSS used in the present study was made of neoprene, similar to the wetsuits, the TSS could limit the water inflow to the clothed body parts and attenuate the convective and conductive heat loss and thus maintain a higher T ළ sk .…”
Section: Body Temperaturesupporting
confidence: 89%
“…Several studies reported that exercise in water decreases I suit because of water leakage (Wolff et al, 1985), however even the I suit values of wetsuits during water exercise calculated in those studies were significantly higher than those of the TSS condition during immersion at rest in the present study (Yeon et al, 1987;Kang et al, 1983;Shiraki et al, 1986;Arieli et al, 1995). These data suggest that the TSS in the present study had significantly lower I suit than any other wetsuits in those previous studies.…”
Section: Thermal Insulationcontrasting
confidence: 63%
See 3 more Smart Citations